Advance Remote Control Home Appliance Switching System Using Radio Frequency and Bluetooth - Sankar Bhunia, Siddhartha; Samanta, Annesa; Ghosal, Suman; Mandal, Kallol (International Journal of Computer Sciences and Engineering, 2025)
As the world gets more and more technologically advanced, we find new technology coming in deeper and deeper into our personal lives even at home. Modern houses are gradually shifting from conventional switches to wireless controlled switches. This is the advance switching system in today’s technology. In this paper, we present the design and implementation of a low cost but flexible home automation system using Radio Frequency and Bluetooth. We are controlling our home appliance using a simple circuit, which consists of RF transmitter (TX02) and RF receiver (ROHS) and also with Bluetooth which can transmit and receive. It is Atmega 8 Microcontroller based circuit. This system is designed to be scalable allowing variety of devices to be controlled with minimum change to its core.